Research methods of ski resorts’ visual perception - Onufriv, Yaryna (Lviv Polytechnic Publishing House, 2015)
The paper describes the research methods of visual perception of ski complexes. It explains the basic paradigms of visual research in the context of the problem of visual impact of ski complexes on natural mountain environment.
Keywords: visual impact; research methods; paradigm; expert approach; public preferences